POLA JELAJAH ORANGUTAN (Pongo pygmaeus morio) DI STASIUN PENELITIAN MENTOKO DAN PREFAB TAMAN NASIONAL KUTAI, KALIMANTAN TIMUR - Agnes Ferisa; Ani Mardiastuti; Entang Iskandar (Department of Forest Resources Conservation and Ecotourism - IPB University, 2014)
The purpose of this research were to measure orangutan daily range, home range, core area and overlapping between individu. Research was conducted May-September 2012, collected 415,67 hours of focal data on 3 orangutans in each research station site. Ranging data were collected by focal animal sampling and analyzed by ArcGIS and kernel density estimation (kde). The result shows that mean of daily range in Mentoko was 0.563 km/day (range 0,339 km/day-0,749 km/day), and Prefab was 0.609 km/day (range 0,423 km/day-0,570 km/day). Mean home range in Mentoko was 0, 169 km2 (range 0,045 km2-0,401 km2) with core area 0,045 km2 (range 0,007 km2-0,113 km2), and Prefab was 0,117 km2 (range 0,061 km2-0,197 km2) with core area 0,038 km2 (range 0,009 km2-0,079 km2). Overlapping in Mentoko was occur between Darwin and Putri covering 3.914 ha. Prefab overlay was occur between Bayur and Labu 5.239 ha, Bayur and Mawar 5.848 ha. Key words: Core area, Daily range, Home range, Kutai National Park, overlapping, Pongo pygmaeus morio.